2022
DOI: 10.1093/sleep/zsab293
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating perinatal Insomnia Disorder and sleep disruption: a longitudinal study from pregnancy to 2 years postpartum

Abstract: Study Objectives Insomnia Disorder diagnoses require persistent sleep complaints despite “adequate sleep opportunity”. Significant perinatal sleep disruption makes this diagnosis challenging. This longitudinal study distinguished between Insomnia Disorder and Perinatal Sleep Disruption and their sleep and mental health correlates. Methods 163 nulliparous females (age M±SD=33.35±3.42) participating in a randomised-controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…Indeed, our estimated rate of 19.2% was lower than a recent meta-analytic estimate of 27.2% prevalence of clinically significant insomnia in the second trimester [ 1 ]. However, our rate of 19.2% is highly consistent with a recent estimate of 16-20% for DSM-5 insomnia disorder in late pregnancy as diagnosed by clinical interview [ 3 ]. These data suggest that our operationalization of survey-assessed DSM-5 insomnia disorder yields estimates consistent with rates derived from clinical interviews; this finding may inform epidemiological efforts in this patient population going forward.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Indeed, our estimated rate of 19.2% was lower than a recent meta-analytic estimate of 27.2% prevalence of clinically significant insomnia in the second trimester [ 1 ]. However, our rate of 19.2% is highly consistent with a recent estimate of 16-20% for DSM-5 insomnia disorder in late pregnancy as diagnosed by clinical interview [ 3 ]. These data suggest that our operationalization of survey-assessed DSM-5 insomnia disorder yields estimates consistent with rates derived from clinical interviews; this finding may inform epidemiological efforts in this patient population going forward.…”
Section: Discussionsupporting
confidence: 91%
“…As such, future research should determine whether these results replicate when DSM-5 insomnia disorder is diagnosed via clinical interviews. Even so, it is worth emphasizing that our estimated rates of DSM-5 insomnia disorder are consistent with rates derived from clinician-administered diagnostic interviews of pregnant women of similar gestational age [ 3 ]. And notably, the technique employed in the present study has been supported by large-scale epidemiological studies [ 38 , 39 ], and the empirically derived quantitative cutoffs identified in this report are consistent with prior psychometric validation of the ISI and PSQI [ 33 , 40 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As an understudied area, large‐scale longitudinal studies were welcomed. Diagnosing insomnia during pregnancy is challenging, particularly in the perinatal period where sleep disruption is common 35 . A cross‐sectional analysis of US pregnancy‐related hospitalisations spanning 12 years revealed that not only did a coded diagnosis of insomnia during pregnancy increase over the study period, but it was an independent predictor of severe maternal morbidity 36 .…”
Section: Insomniamentioning
confidence: 99%